LED Lights Enhance Metabolites and Antioxidants in Chinese Cabbage and Kale - Min Ki Lee; Mariadhas Valan Arasu; Suhyoung Park; Dong Hae Byeon; Sun-Ok Chung; Sang Un Park; PyoLim Yong-; JuKim Sun- (Brazilian Archives of Biology and Technology)
Light emitting diode (LED) lights play an important role in the plant physiology and alter the metabolites in a significant manner. Glucosinolates (GSLs), polyphenols, flavonoids and antioxidant properties of Chinese cabbage and kale cultivated in varying LED lights were investigated. Analysis revealed 7 aliphatic, 3 indolyl and 1 aromatic GSLs in Chinese cabbage and kale. The total GSL content ranged from 1.5-19.08 and 1.85-24.87 µmol/g DW, and glucobrassicanapin was the predominant GSL (3) in Chinese cabbage, whereas; sinigrin (3.49 µmol/g DW) was in kale. Blue and red LED lights produced significantly higher amount of GSLs in Chinese cabbage and kale respectively. Results revealed higher amount of total polyphenol (3.845 µg/mL) and total flavanoids (3.939 μg/mL) in Chinese cabbage. Chinese cabbage and kale showed signiﬁcant antioxidant activities when compare with positive control, and the antioxidant assays were slightly correlated with total GSLs, polyphenols and flavanoids contents. The influence of LED lights on glucobrassicin in Chinese cabbage and kale should be studied extensively, because GSL is the precursor of indole-3-carbinol, a potent anticancer isothiocyanate.